Brain SPECT scans in students with specific learning disability: Preliminary results - Karande, S; Deshmukh, N; Rangarajan, V; Agrawal, A; Sholapurwala, R (Journal of postgraduate medicine, 2019)
Background and Objectives: Brain single-photon emission computed tomography (SPECT) assesses brain function through measurement of regional cerebral blood flow. This study was conducted to assess whether students with newly diagnosed specific learning disability (SpLD) show any abnormalities in cerebral cortex perfusion. Settings and Design: Cross-sectional single-arm pilot study in two tertiary care hospitals. Subjects and Methods: Nine students with SpLD were enrolled. Brain SPECT scan was done twice in each student. For the first or "baseline" scan, the student was first made to sit with eyes open in a quiet, dimly lit room for a period of 30-40 min and then injected intravenously with 20 mCi of 99mTc-ECD. An hour later, "baseline scan" was conducted. After a minimum gap of 4 days, a second or "test scan" was conducted, wherein the student performed an age-appropriate curriculum-based test for a period of 30-40 min to activate the areas in central nervous system related to learning before being injected with 20 mCi of 99mTc-ECD. Statistical Analysis Used: Cerebral cortex perfusion at rest and after activation in each student was compared qualitatively by visual analysis and quantitatively using NeuroGam™ software. Results: Visual analysis showed reduction in regional blood flow in temporoparietal areas in both "baseline" and "test" scans. However, when normalization was attempted and comparison done by Talairach analysis using NeuroGam software, no statistically significant change in regional perfusion in temporoparietal areas was appreciated. Conclusion: Brain SPECT scan may serve as a robust tool to identify changes in regional brain perfusion in students with SpLD.